Zygomatic implant-retained fixed complete denture for an elderly patient - Baig, M.R.; Rajan, G.; Yunus, N. (Wiley, 2012)
Dental rehabilitation of a completely edentulous geriatric patient has always been a challenge to the clinician, especially in treating those with higher expectations and demands. Treatment duration and the amount of residual alveolar bone available are often important considerations when planning for dental implant-based fixed treatment for these patients. With the introduction of zygomatic implants, a graftless alternative solution has emerged for deficient maxillary bone with provision for immediate loading. This article describes the treatment of a completely edentulous elderly patient using zygomatic implants in conjunction with conventional implants. The implants were immediately loaded using a definitive acrylic resin fixed denture reinforced with a cast metal framework, to provide function and aesthetics.